Laparoscopic hysterectomy - Seminario, Jaime (2015)
Viability of laparoscopic hysterectomy has been ascertained since Reich’s original publication. There exists though considerable debate in relation to indications. Laparoscopic hysterectomy’s objective is to reduce frequency of abdominal hysterectomy in order to decrease abdominal wall complications, less pain, faster recovery, return to work in one week. When laparoscopic hysterectomy is indicated, type of surgery is the result of various factors’ analysis like uterine size and motility, vaginal access and surgeon experience with each hysterectomy modality susceptible to laparoscopy. Encouraging results should not make us forget that it is a major complex technique that implies more training and experience and its performance should be reserved to surgeons who have developed necessary ability in complex laparoscopic procedures.